Effect of yearly milk per cow on various reproduction traits - Edward P. Call (Kansas Agricultural Experiment Station Research Reports, 1994)
An analysis of 4,334 Holstein dairies confirms the negative genetic correlation that exists between milk production and reproduction. The most obvious traits affected are services per conception and conception rate. When subjected to analysis by the KSU Dairy Herd Analyzer (DHA) program, higher-producing herds have less economic loss because their managers do a better job of controlling factors not under genetic control, such as average days dry and age at calving of first-calf heifers (L-1). Higher-producing herds also have fewer cows that are open and should be bred.; Dairy Day, 1994, Kansas State University, Manhattan, KS, 1994;
Keywords: Dairy Day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-141-S; Report of progress (Kansas Agricultural Experiment Station); 716; Milk production; Genetics; production; Reproductive losses